Interview mit Muraina Oyelami, Siegrun Salmanian und Lena Naumann (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2017)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Interviews; Art; Africa; Artists; Exhibitions; Art Exhibition; Nigeria; Cultural Centre; Performing Arts Center; Art Collector; Art Collecting